#TITLE_ALTERNATIVE# - KURNIA (NIM 10202054), ADE
Radiation commonly described as something dangerous for common people because it is always be assosiated with the Hiroshima-Nagasaki A Bomb and the Chernobyl nuclear leak. In fact, radiation is a verb that shows the acts of emitting wave or particle. Lights is one example of radiation, that is electromagnetic wave. But the writer focus on radiation that is emitted by radionucleid. Radiation from radionucleid is commonly used for cancer theraphy. Instead, it is also can be used to decet material flaws that cannot be defined visually without destructing the material (non-destructive technique). This is what the paper talked about. By utilizing a detector (radiation counter) and a radionucleid that emits gamma ray, material flaws can be detected. The detector is a radiation counter that is similar to Geiger Muller tube and the radionucleid is Cobalt-60. Material tested is put between the radionucleid and the detector, so we can compare the intensity of the radiation; before and after it moving through the material. The absorption coefficient, a characteristic of material, can be compared to the standard. Radionucleid emits radiation randomly; means radiation emitted has the same probility for any counts so the acquired data will have uncertainty rates. Because of that, statistical analysis is required to test the data validity. Datas are also compared with material standard; the same material that is proven not to have flaws. Statistical analysis to be done are poisson distribution, gaussian distribution, ?2-test and t-test. By statistical analysis, we hope that the flaws existent in the material is trustworthy.